Analisis Sistem Informasi Akuntansi Pengeluaran Kas pada Proses Verifikasi Surat Perintah Membayar (SPM) untuk Pencairan Dana Pihak Ketiga di Dinas Pekerjaan Umum dan Penataan Ruang Kota Palembang - Septiani Fransisca; Putri Salsabila; Lia Sari (Jurnal Kendali Akuntansi, 2026)
This article examines how the cash-disbursement accounting information system is used in the verification of Payment Order Letters (SPM) for third-party payments at the Public Works and Spatial Planning Office of Palembang City. The study applies a descriptive qualitative method based on internship observations, interviews, document review, and relevant literature. The discussion indicates that the Online SPM application has become the main medium for submitting, checking, authorizing, and following up payment documents until the issuance of Fund Disbursement Orders (SP2D). The control process is reflected in role separation between the technical unit, finance staff, BPKAD verifier, and approving officer, as well as in layered document checks and electronic monitoring. Nevertheless, several practical issues still occur, including budget-code inconsistencies, inaccurate bank-reference data, incomplete supporting files, expired tax billing documents, and input mistakes in the system. The study concludes that the system has supported accountability in regional cash disbursement, but document discipline, early checking, and coordination among work units still need strengthening.